Tumors vs. Chronic Wounds: An Immune Cell's Perspective - Hua, Yichao; Bergers, Gabriele (Frontiers in Immunology, 2019)
The wound repair program is tightly regulated and coordinated among different cell constituents including epithelial cells, fibroblasts, immune cells and endothelial cells following consecutive steps to ensure timely, and proper wound closure. Specifically, innate and adaptive immune cells are pivotal participants that also closely interact with the vasculature. Tumors are portrayed as wounds that do not heal because they undergo continuous stromal remodeling and vascular growth with immunosuppressive features to ensure tumor propagation; a stage that is reminiscent of the proliferative resolution phase in wound repair. There is increasing evidence from mouse model systems and clinical trials that targeting both the immune and vascular compartments is an attractive therapeutic approach to reawaken the inflammatory status in the “tumor wound” with the final goal to abrogate tumor cells and invigorate tissue homeostasis. In this review, we compare the implication of immune cells and the vasculature in chronic wounds and tumor wounds to underscore the conceptual idea of transitioning tumors into an inflammatory wound-like state with antiangiogenic immunotherapies to improve beneficial effects in cancer patients.